Physician Decision-making in Return to Play After Cervical Spine Injury: A Descriptive Analysis of Survey Data. Issue 7 (August 2020) - Ukogu, Chierika; Bienstock, Dennis; Ferrer, Christopher; Zubizarreta, Nicole; McAnany, Steven; Chaudhary, Saad B.; Iatridis, James C.; Hecht, Andrew C.
Abstract : Summary of Background Data: Cervical spine injuries commonly occur during athletic play, and such injuries carry significant risk for adverse sequelae if not properly managed. Although guidelines for managing return to play exist, adherence among spine surgeons has not been thoroughly examined. Study Design: Prospective analysis of survey data collected from surgeon members of the Cervical Spine Research Society (CSRS) and the International Society for the Advancement of Spine Surgery (ISASS). Objective: The objective of this study was to characterize consensus among spine surgeons regarding decision-making on return to competitive sports and level of impact following significant cervical spine injuries from real-life scenarios. Materials and Methods: Return to play decisions for 15 clinical cervical spine injury scenarios were compared with current guidelines. Surgeon demographic information such as orthopedic board certification status and years in practice were also analyzed. Weighted kappa analysis was utilized to determine interrater reliability in survey responses. Results: Survey respondents had a poor agreement with both Watkins and Torg guidelines (average weighted κ of 0.027 and 0.066, respectively). Additional kappa analysis of surgeon agreement regarding the "Types of Play" and "Level of Play" for return was still remained poor (Kendall W of 0.312 and 0.200, respectively). Responses were also significantly influenced by surgeon demographics. Conclusions: There is poor consensus among spine surgeons for return to play following cervical spine injury. These results support the concept that given the gravity of cervical spine injuries, a more standardized approach to decision-making regarding return to play after cervical spine injury is necessary.